INTERNAL RESEARCH BUDGET PROPOSAL FEATURES DEVELOPMENT ON RESEARCH AND COMMUNITY OUTREACH SERVICES WEB-BASED INFORMATION SYSTEM AT PRIVATE CAMPUS - Noveriyanti, Dea; Wiratama, Jansen; Permana, Angga Aditya; Wijaya, Santo Fernandi; Nugroho, Antonius Sony Eko (IJISCS (International Journal of Information System and Computer Science), 2023)
Service processes using conventional methods have many limitations and have the potential to result in data accumulation and repetitive work. Transforming a service model that initially used Linktree into an Information System has become necessary for the Research and Community Service Institute (LPPM) of Multimedia Nusantara University (UMN). One of the features developed is the budget Proposal of Internal Research service feature. The Agile Development Method, a renowned software development methodology, is used to optimize the feature development of the RCOS Information System. The development process is carried out by benchmarking, user interviews, and prototyping, following the stages contained in the Agile Development Method. The leverage of the Laravel framework and Tailwind CSS play a pivotal role in developing a website-based RCOS information system. The service model was successfully transformed using the RCOS feature, and the test results with the User Acceptance Test (UAT) show that the Budget Proposal of Internal Research features in the RCOS information system can function well following the UMN LPPM service needs.